Current trends in female entrepreneurship : innovation and immigration - Mari, Michela; Poggesi, Sara (Entrepreneurial behaviour series., 2024)
The area of female entrepreneurship has been the topic of academic debate and support from the United Nations, European Union and other international bodies, for benefits such as economic growth, creation of new jobs, increasing gender equality and decreasing levels of poverty. While acknowledgement of the contributions of female entrepreneurship is present in academic research, Michela Mari and Sara Poggesi uncover two under-researched aspects: innovation in female entrepreneurship and immigrant female entrepreneurship. Regarding innovative women entrepreneurs, policy makers agree on the socio- economic relevance of such entrepreneurs as they contribute to the economic and social growth of a country and act as mentor for younger girls. However, there are few studies to date on the intertwinement among innovation, gender, and entrepreneurship in management studies. Regarding immigrant women entrepreneurs, policy makers agree on the socio-economic relevance of entrepreneurship for these women as a pathway towards employment, empowerment, and gender equality. However, also in this case, there is still much to learn about how to mobilize such forces. The Entrepreneurial Behaviour series is focused on expanding the scope of Entrepreneurial Behaviour theory and analysis and enriching practice by encouraging multi-cultural and multi-disciplinary approaches.